1991
DOI: 10.3181/00379727-198-43297
|View full text |Cite
|
Sign up to set email alerts
|

Significant Qualitative Differences Exist between Thyrotropin and Prolactin Secretory Dynamics Induced by Pituitary Cell Swelling

Abstract: Cell swelling produced by a variety of techniques is a potent stimulus intensity-related inducer of an immediate secretory burst of thyroid-stimulating hormone (TSH) and prolaction (PRL) secretion from anterior pituitary cells. A 2-min "square wave" exposure to either hyposmolarity or isotonic urea induced stimulus intensity-correlated TSH and PRL secretory bursts peaking within 3 min, but the PRL zenith occurred 1 min later than that of TSH. With continuous exposure to these stimuli, TSH secretion rapidly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In many cells placed in hyposmotic media, the initial swelling due to water influx is followed rapidly by losses of ions and/or organic solutes that lead to RVD (19,20). In many cell types, RVD is observed within 20 min of hyposmotic stimulation (2,20,21,32,37,39). The absence of a rapid RVD in the PRL cell may reflect the smaller shift in osmolality used in this study (15% reduction in osmolality) compared with those typically used by others, i.e., 25-50% (2, 20, 21, 31, 32, 39).…”
Section: Discussionmentioning
confidence: 99%
“…In many cells placed in hyposmotic media, the initial swelling due to water influx is followed rapidly by losses of ions and/or organic solutes that lead to RVD (19,20). In many cell types, RVD is observed within 20 min of hyposmotic stimulation (2,20,21,32,37,39). The absence of a rapid RVD in the PRL cell may reflect the smaller shift in osmolality used in this study (15% reduction in osmolality) compared with those typically used by others, i.e., 25-50% (2, 20, 21, 31, 32, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated prolactin release from isolated tissue (18,34,41,42) or cells in response to hyposmotic stimulation (41,50), which required extracellular calcium (23,40,41). While these findings suggest that prolactin is likely released by exocytosis in response to hyposmotic stress, secretory activity at the single vesicle level in response to hypotonicity was not monitored directly yet.…”
mentioning
confidence: 94%
“…For ramp expo¬ sure, a gradient-maker originally designed to make sucrose concentration gradients for ultracentrifugation was used to gradually increase the concentration of stimulator. The final concentration was the same as that achieved with square-wave exposure (Wang et al 1991). Comparison of the dynamics of concentrations achieved in the perifusion chamber effluent using the square-wave or ramp system is shown in Fig.…”
Section: Monitoring ¡Ca ]¡mentioning
confidence: 97%
“…We have found a marked difference in the dynamic secretory pattern of PRL secretion induced by squarewave compared with ramp application of an osmotic stimulus (Wang et al 1991). In this study we have compared the dynamics of changes in [Ca ]¡ and PRL secretion in response to square-wave or ramp exposure to TRH or depolarizing .…”
Section: Introductionmentioning
confidence: 98%